Oligosaccharides in goat milk: structure, health effects and isolation - Kiskini, A.; Difilippo, E. (Cellular and Molecular Biology, 2013)
Oligosaccharides have been widely recognized for their prebiotic and anti-infective properties. Among the different types of mammalian milk, the one of humans is the richest source of naturally derived oligosaccharides. However, their use as a basis for functional foods is hampered, due to their structural complexity, which in turn makes their re-synthesis extremely difficult. Thus, oligosaccharides from other sources have to be used. In this sense, goat milk constitutes a very appealing candidate, as it contains the highest amount of oligosaccharides among domestic animals, while goat milk oligosaccharides show significant similarities to human milk oligosaccharides from a structural point of view. Studies on goat milk oligosaccharides are scant, and more data is required in order to provide solid clinical evidence of their beneficial effects on humans. The aim of this review is to collect and present the main research findings on goat milk oligosaccharides structure, health effects and isolation.